2001
DOI: 10.2116/analsci.17.1309
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Spectrophotometric Method for the Determination of Selenium

Abstract: Selenium is widely distributed in nature in relatively small concentrations in rocks, plants, coal and other fossil fuels. Selenium compounds are extensively used in paints, dyes, glass, electricals, rubber and insecticides, and in many other industries. 1 The determination of selenium is of considerable interest because of its contrasting biological effects; selenium is a toxic element as well as a trace element for animals and humans.2 Its efficiency causes pulmonary edema, abdominal pain, jaundice, chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 12 publications
0
30
0
1
Order By: Relevance
“…The proposed method provides a limit of detection of the same order than that obtained by using NPDPTC after a previous separation of the gas phase generation, 9 and clearly lower than other photometric procedures. 3,7,8 It seems that kinetic spectrophotometric approaches provide an enhancement of the LOD and astonishing the sensitivity reported for FIA spectrophotometric determination with MBTH is one order of magnitude better than that obtained by us. However, on looking through the aforementioned study, 12 it can be seen that authors reported a sensitivity of 0.1875 for the concentration range between 0.050 and 0.500 mg L -1 which is clearly lower than the value of 0.501 obtained in this study for the range between 0.010 and 0.500 mg L -1 and thus it is surprising that they could found a LOD of 0.00025 mg L -1 nor for using a 2σ criterion.…”
Section: Effect Of Reagent Concentrationmentioning
confidence: 59%
“…The proposed method provides a limit of detection of the same order than that obtained by using NPDPTC after a previous separation of the gas phase generation, 9 and clearly lower than other photometric procedures. 3,7,8 It seems that kinetic spectrophotometric approaches provide an enhancement of the LOD and astonishing the sensitivity reported for FIA spectrophotometric determination with MBTH is one order of magnitude better than that obtained by us. However, on looking through the aforementioned study, 12 it can be seen that authors reported a sensitivity of 0.1875 for the concentration range between 0.050 and 0.500 mg L -1 which is clearly lower than the value of 0.501 obtained in this study for the range between 0.010 and 0.500 mg L -1 and thus it is surprising that they could found a LOD of 0.00025 mg L -1 nor for using a 2σ criterion.…”
Section: Effect Of Reagent Concentrationmentioning
confidence: 59%
“…In this work, the liberated iodine was allowed to react with the VB dye in the presence of sodium acetate (reaction 2). Variamine blue is known to be a suitable chromogenic reagent for iodine (Revansiddapa and Kumar 2001;Narayana and Cherian 2005;Coo and Martinez 2004). The liberated I 2 oxidizes the dye to a violet color whose absorbance maxima is at 550 nm.…”
Section: Iodometric Reactionmentioning
confidence: 99%
“…The slope of the calibration curve leads to a molar absorptivity of 1.47 x 10 6 L mol -1 cm -1 . The Sandell's sensitivity [18], detection limit (D L = 3.3 σ/m) and quantitation limit (Q L = 10 σ/m), where σ = standard deviation of the reagent blank and m = slope of calibration curve [19] were found to be 4.3 x 10 -5 µg cm -2 , 0.001 µg mL -1 and 0.0043 µg mL -1 , respectively.…”
Section: Spectral Characteristicsmentioning
confidence: 99%